Identifikasi dan Penentuan Indeks Hidrolisis Protein pada Bakteri Proteolitik dari Tanah Mangrove di Margomulyo, Balikpapan - Utami Sri Hastuti; Febriani Sarwendah Asri Nugraheni; Putri M. Al Asna (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2017)
Mangrove has a function as a physical protector of the seashore and also play a role as a habitat of various typesof aquatic fauna. The decaying mangrove stems contain vegetable protein and mixed with animal proteinderived from dead animals in mangrove soil. Proteolytic bacteria play a role in the process of proteindegradation into more simple and soluble compounds. This research aims to: 1) identify species of proteolyticbacteria in mangrove soil, 2) count the Protein Hydrolysis Index on each species of proteolytic bacteria, 3)determine the most potential proteolytic bacteria species to decompose the protein. Soil samples were takenfrom 10 points of mangrove area Margomulyo, Balikpapan. After that, soil samples were diluted in 10-1 to 10-10 and 0,1 mL of each level dilution is inoculated to the NA medium, incubated at 37°C for 1 x 24 hours. Eachcolony sorts were isolated, identified and determined the proteolytic bacteria isolates, then the ProteinHydrolysis Index on the Skim Milk Agar medium were count. The research results showed that: 1) there are 7species of proteolytic bacteria from mangrove soil, 2) the Protein Hydrolysis Index of each species ofproteolytic bacteria ranged from 1.62 to 2.94, and 3) Vibrio parahaemolyticus is the most potential proteolyticbacteria with the Protein Hydrolysis Index is 2,94